Optimizing Enchanced Recovery After Caesarean Section (ERACS): an Important-Performance Mapping Analysis (IPMA) Approach - Tansya Sushan Purnaningrum; Ferdi Antonio (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
Enhanced Recovery After Caesarean Section (ERACS) is an evidence-based, multidisciplinary approach aimed at accelerating postoperative recovery without compromising patient safety. This study employed a descriptive qualitative method through a narrative literature review. The findings highlight three key factors for successful ERACS implementation: clinical autonomy of obstetricians, which allows for more adaptive and patient-centered decisions; patient experience, supported by effective communication and involvement in decision-making; and hospital efficiency, including optimized scheduling, resource availability, and interprofessional collaboration. These components are interrelated and mutually reinforce ERACS outcomes. Recommendations include continuous training for healthcare providers, development of evidence-based clinical guidelines, and increased patient engagement.